The Relationship between Progressivism Educational Philosophy and Science and Its Relevance in the Era of the Industrial Revolution 4.0 (Society 5.0) - Syahidi, Khaerus; Sarjan, Muhammad; Rokhmat, Joni; A, Syahrial; Mertha, I Gde; Arizona, Kurniawan; Syamsuddin, Syamsuddin; Sucilestari, Ramdhani (Universitas Hamzanwadi, 2023)
Philosophy and science are human efforts to understand the concepts and methods of a scientific discipline. Changing times and developments have ushered in a philosophy of configuration by showing how the